2012
DOI: 10.1186/1471-2407-12-90
|View full text |Cite
|
Sign up to set email alerts
|

Survival of gastrointestinal stromal tumor patients in the imatinib era: life raft group observational registry

Abstract: Background Gastrointestinal stromal tumors (GIST), one of the most common mesenchymal tumors of the gastrointestinal tract, prior to routine immunohistochemical staining and the introduction of tyrosine kinase inhibitors, were often mistaken for neoplasms of smooth muscle origin such as leiomyomas, leiomyosarcomas or leiomyoblastomas. Since the advent of imatinib, GIST has been further delineated into adult- (KIT or PDGFRα mutations) and pediatric- (typified by wild-type GIST/succinate dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
3
32
1
Order By: Relevance
“…Consistent with this hypothesis, Call et al found that among pediatric GIST cases, patients were predominately female. 22 While our study included no pediatric cases of GIST, it is possible that GISTs <2 cm share more characteristics with pediatric GIST as opposed to adult GIST, thus shifting the sex distribution. In terms of racial differences, malignant GISTs <2 cm were more common in Blacks as compared to Whites, consistent with our earlier finding in all patients with GIST.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this hypothesis, Call et al found that among pediatric GIST cases, patients were predominately female. 22 While our study included no pediatric cases of GIST, it is possible that GISTs <2 cm share more characteristics with pediatric GIST as opposed to adult GIST, thus shifting the sex distribution. In terms of racial differences, malignant GISTs <2 cm were more common in Blacks as compared to Whites, consistent with our earlier finding in all patients with GIST.…”
Section: Discussionmentioning
confidence: 98%
“…Though complete surgical resection is feasible in a substantial proportion of GISTs, relapses are common, especially with high-risk GISTs (2). Surveillance with imaging in these patients can help in timely detection of relapses.…”
Section: Surveillancementioning
confidence: 99%
“…Though initially labeled histologically as leiomyosarcomas, the identification of unique activating mutations in KIT gene enabled classification of GIST as a distinct entity (1). GIST like other soft tissue sarcomas was conventionally associated with poor prognosis with a 5-year survival of 5–20% mainly due to resistance to conventional chemotherapy and radiotherapy (23). The discovery of imatinib mesylate which is a small molecule inhibitor of receptor tyrosine kinases (RTK) notably KIT dramatically changed the outcome of patients with GIST (4).…”
Section: Introductionmentioning
confidence: 99%
“…A log-rank test was used to test for significant prognostic ability of baseline D-dimer levels. Adjustment for baseline clinical characteristics previously identified as prognostic in advanced GIST was undertaken using the Cox proportional hazards model [11][12][13] . Genetic mutation analysis was not conducted in patients diagnosed early in the series therefore this was not considered.…”
Section: Discussionmentioning
confidence: 99%